Adoção tardia nas famílias contemporâneas - Ferreiro, Conchita Pinheiro Garcia (2021)
This study aims to reflect on the difficulties of late adoption in contemporary families. It is qualitative research aimed at deepening the understanding of late adoption and its difficulties, in particular those related to the formation of emotional bonds. Authors who turned their attention to the subject were consulted, namely, René Spitz, John Bowlby and Donald Winnicott, whose thinking was articulated with the main obstacles and difficulties in the adoption of older children. The discussion turned to the vicissitudes of late adoption and how psychologists can intervene to promote a more satisfactory process for those involved: the child to be adopted and the adopting family